2022
DOI: 10.1002/er.7878
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of graphene material in PCM with aluminum fin structure for improving the battery cooling performance

Abstract: Summary Phase change material (PCM) based battery thermal management system (BTMS) provides even heat distribution and lower maximum temperature, but it suffers from low thermal conductivity. In this study, the impact of graphene additive on PCM was analyzed by presenting three experiments with various structures to solve PCM's low thermal conductivity problem. The results demonstrate that there is no positive impact of graphene additive in the first and third structures. The PCM‐graphene additive between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…After the normalization of the data, the grey correlation coefficient (𝜉 ), which relates the ideal and real normalized experimental results, was calculated with the help of Equation (20). (21) is the deviation between 𝑦 (𝑘) and 𝑦 (𝑘).…”
Section: General Evaluations Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the normalization of the data, the grey correlation coefficient (𝜉 ), which relates the ideal and real normalized experimental results, was calculated with the help of Equation (20). (21) is the deviation between 𝑦 (𝑘) and 𝑦 (𝑘).…”
Section: General Evaluations Of the Resultsmentioning
confidence: 99%
“…As the temperature increases, the PCM absorbs the heat and changes from solid to liquid state; in the opposite case, heat is given to the environment by the exothermic process, and it returns to the solid state [19]. Aslan et al [20] investigated the effect of graphene additives on PCM with three different mechanisms to increase the low thermal conductivity of PCM. They observed that the first and third designs did not have a noticeable contribution to heat transfer, but the second design supplemented with PCMgraphene significantly improved the heat transfer and provided faster cooling.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pollution gas produced by its consumption will cause global warming, lead to the greenhouse effect, and lead to many disasters such as the continuous disappearance of glaciers and frozen soil, rising sea level and frequent extreme weather [1]. At present, the trend of energy development is changing, from developing new energy sources such as solar energy, hydro energy and wind energy to developing materials and devices based on electrochemical energy storage [2]. There are many kinds of electrochemical energy storage devices, such as Li-lon, electrochemical capacitors and fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…The BTMS can be classified in terms of power consumption, working fluid, and arrangement [25]. There are various cooling methods suggested for battery thermal management systems, including air cooling [26][27][28][29][30][31], liquid cooling [32][33][34][35], PCM (phase-change material) [36][37][38], heat pipes [39,40], and thermoelectric coolers [41]. Each method has advantages and disadvantages in terms of its application area [42][43][44].…”
Section: Introductionmentioning
confidence: 99%